Three years into the pandemic: results of the longitudinal German COPSY study on youth mental health and health-related quality of life - Ravens-Sieberer, Ulrike; Devine, Janine; Napp, Ann-Kathrin; Kaman, Anne; Saftig, Lynn; Gilbert, Martha; Reiß, Franziska; Löffler, Constanze; Simon, Anja Miriam; Hurrelmann, Klaus; Walper, Sabine; Schlack, Robert; et al. (Frontiers in Public Health, 2023)
Purpose For the past three years, the German longitudinal COPSY (COVID-19 and PSYchological Health) study has monitored changes in health-related quality of life (HRQoL) and the mental health of children and adolescents during the COVID-19 pandemic. Methods A nationwide, population-based survey was conducted in May–June 2020 (W1), December 2020–January 2021 (W2), September–October 2021 (W3), February 2022 (W4), and September–October 2022 (W5). In total, n = 2,471 children and adolescents aged 7–17 years (n = 1,673 aged 11–17 years with self-reports) were assessed using internationally established and validated measures of HRQoL (KIDSCREEN-10), mental health problems (SDQ), anxiety (SCARED), depressive symptoms (CES-DC, PHQ-2), psychosomatic complaints (HBSC-SCL), and fear about the future (DFS-K). Findings were compared to prepandemic population-based data. Results While the prevalence of low HRQoL increased from 15% prepandemic to 48% at W2, it improved to 27% at W5. Similarly, overall mental health problems rose from 18% prepandemic to W1 through W2 (30–31%), and since then slowly declined (W3: 27%, W4: 29%, W5: 23%). Anxiety doubled from 15% prepandemic to 30% in W2 and declined to 25% (W5) since then. Depressive symptoms increased from 15%/10% (CES-DC/PHQ-2) prepandemic to 24%/15% in W2, and slowly decreased to 14%/9% in W5. Psychosomatic complaints are across all waves still on the rise. 32–44% of the youth expressed fears related to other current crises. Conclusion Mental health of the youth improved in year 3 of the pandemic, but is still lower than before the pandemic.